The Wahhabi Movement in India, 1st edition - Ahmad, Qeyamuddin (Routledge, 2020)
Founded by Sayyid Ahmad (1786-1831) of Rae Bareli, the Wahhabi Movement in India was a vigorous movement for socio-religious reforms in Indo-Islamic society in the nineteenth century with strong political undercurrents. It stood for a strong affirmation of Tauhid (unity of God), the efficacy of ijtihad (the right of further interpretation of the Quran and the Sunnah, or of forming a new opinion by applying analogy) and the rejection of bid'at (innovation). It remained active for half a century.